Crisis Communication and Response Strategies in Car Manufacturing Companies: A Multiple Case-Study Approach in Gauteng, South Africa - Khuzwayo, Talent Sinenhlanhla; Isheloke, Byelongo Elisée (International Journal of Mass Communication, 2026)
South Africa has several car manufacturing companies or plants, referred to as open systems, and in fact, the automotive industry is the biggest employer in the country with 120 000 employees and a 6.4% stake of the national GDP (against 8% of the mining sector, 5 years ago). Although its contribution to the economic prospects of this nation is undeniably huge (more or less 14.2% of national exports and 24% of manufacturing output), the car manufacturing industry also comes with its own challenges and, at worse, crises. This study, amongst the other things, sought to address car manufacturing crises by looking into four car manufacturing companies’ chaotic situations and related theories. The research shows that crises are inevitable in business and industry alike. It also demonstrates that crisis communication steps and response strategies thereof, if followed and adhered to, could help to better understand potential crises, avoid them, address them at hand or in their aftermath. Through this research, it is obvious that the car manufacturing industry, specific models tend to have potentially fatal defects, leading to numerous car recalls as shown in selected case studies. This research followed a multiple case study and qualitative approach. The research was conducted by administering semi-structured indepth interviews, doing thematic and content analyses of obtained raw data, making sense of them and infering/deriving knowledge for all to use. The participants were four car manufacturing companies (herein referred to as Companies A, B, C and D) with their head offices in Gauteng, South Africa. The crisis management teams were selected as the target population because they actively attempt to remedy the crises and interact with various organisational stakeholders when a chaos occurs. The findings identified gaps in crisis communication planning and implementation, given the ever-changing business and public relations’ environments in which organisations operate. As a result, recommendations are made to assist public relations and communications practitioners today and in the future to handle various crises effectively. Ultimately, car manufacturing companies will benefit by improving the protection of their organisations and stakeholders from threats, thus reducing those threats’ negative impacts on business and the economy. Future research could be done either at national level to include more car manufacturing companies in order to allow comparison, or selectively across the regions in the continent, to pursue an hybrid study which equally considers crises in the only other truelly African industrial economy, namely Egypt.